Awakened by death life-giving lessons from the mystics - Peterson, Christiana N. (Broadleaf Books, 2020)
Taking readers on a journey through history guided by the mystics, Awakened by Death shows us how our psychological and spiritual relationship to death has changed over time, and helps us to reclaim a healthy engagement with our own mortality. Ultimately, readers will gain a deeper understanding of how facing the fear of death, and embracing rather than eschewing its mysteries, can help us live richer, fuller lives.